(untitled) (Global Journal of Science Frontier Research, 2012)
This study examines the technical and scale efficiencies for a sample of irrigated and rainfed rice farmers in Anambra State, using data envelopment analysis (DEA). Two(2) local government areas were purposively selected; three communities were randomly selected giving a total of six(6) communities. Twenty five(25) rice farmers were randomly selected from each communities to give a sample size of one hundred and fifty. Structured questionnaire was used to elicit information from the respondents. Data were analysed using descriptive statistics and Data Envelopment Analysis. Results show that irrigated rice farmers were more efficient in resources utilization. The result further indicated a significant scope for a reduction in input usage while maintaining the same output levels. Rice farmers’ education level should be improved to enable them take advantage of modern agricultural techniques for improved productivity.